2023
DOI: 10.1155/2023/1027215
|View full text |Cite
|
Sign up to set email alerts
|

Signal Game Analysis between Software Vendors and Third-Party Platforms in Collaborative Disclosure of Network Security Vulnerabilities

Abstract: The global network threat is becoming more and more serious, and network security vulnerability management has become one of the critical areas in the national information security emergency system construction. To guide the third-party sharing platforms regarding network security vulnerability management, this work constructs a signal game model comprising third-party vulnerability sharing platforms and software vendors for vulnerability collaborative disclosures. In addition, we analyze the game strategy sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, in addressing such issues, game theory has become the most suitable and preferred approach that is applicable for studying behavior interactions and strategy selection. Xiong et al [ 48 ] constructed a game model considering third-party vulnerability-sharing platforms and found that security researchers’ vulnerability disclosure behaviors are encouraged by establishing a credit system for patch development and improving the punishment mechanism for dishonesty. Xu et al [ 49 ] developed a game model to confirm government punishment mechanisms can facilitate win-win situations for enterprises and consumers in certain scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, in addressing such issues, game theory has become the most suitable and preferred approach that is applicable for studying behavior interactions and strategy selection. Xiong et al [ 48 ] constructed a game model considering third-party vulnerability-sharing platforms and found that security researchers’ vulnerability disclosure behaviors are encouraged by establishing a credit system for patch development and improving the punishment mechanism for dishonesty. Xu et al [ 49 ] developed a game model to confirm government punishment mechanisms can facilitate win-win situations for enterprises and consumers in certain scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%